POLITISASI BIROKRASI DALAM MUTASI JABATAN STRUKTURAL DI PEMERINTAHAN KABUPATEN TABANAN TAHUN 2021 - Sukaja, Dodok Samdana; Erviantono, Tedi; Noak, Piers Andreas (Jurnal Nawala Politika, 2022)
This study aims to determine the politicization of the bureaucracy in the transfer of structural positions in the government of Tabanan Regency, especially related to the political dilemmas faced by the regional head after the Election of Regional Heads. This study is framed using rational choice theory by Barbara Geddes and faction theory by Francoise Boucek. The research method used in this study is a descriptive method with a qualitative approach. The result of this research is that there is a politician's dilemma from the elected regent regarding the transfer of positions in the government of Tabanan Regency. This is because first, the elected regional head wants to ensure that he will last at least his term of office. Second, creating a political machine that is loyal and will support it. Third, the elected regent wants to create an effective government.